PERUBAHAN KEBIJAKAN PENDAFTARAN TANAH DI KOTA MAKASSAR - Lande, Valentini Febriani Bala (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
This study aims to analyze and describe changes in policy changes in landregistration policies from PRONA (National Agrarian Operations Project) whichis regulated in Ministerial Regulation of ATR/KBPN Number 4 of 2015 toComplete Systematic Land Registration (PTSL) which is affirmed throughMinisterial Regulation of ATR/KBPN Number 6 of 2018 concerning CompleteSystematic Land Registration. This study uses the theoretical perspective of theAdvocacy Coalition Framework (ACF) from Sabatier and colleagues. Theapproach used in this research is a qualitative approach with a case studystrategy. The results of the study indicate that the change in legislation regardingthe registration of land rights is contained in the regulation of the Minister ofAgrarian Affairs and Spatial Planning/Head of the National Land Agency Number 12 of 2017 concerning the Acceleration of the Implementation of CompleteSystematic Land Registration (PTSL). PRONA and PTSL policies are the samepolicy, namely regarding land adjudication, there is only a slight increase in theresults to be achieved later which is not only producing a certificate but alsocarrying out a mapping process to improve data on land in Indonesia which isgrouped into several categories.